2015
DOI: 10.31018/jans.v7i1.577
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly dyeing of wool and pashmina fabric using Quercus robur L. (fruit cups) dye and Salix alba L. (wood extract) mordant

Abstract: Study was conducted to investigate the dyeing potential of Quercus robur L. (fruit cups) dye and Salix alba L. (wood extract) mordant on wool and pashmina fabrics. The experiment was conducted keeping in view the environmental safety by using unutilized plant materials and excluding the usage of chemical agents. The dyeing was carried out individually including and excluding mordant adopting different mordanting methods. The parameters like percent absorption, colour coordinates, colour strength (K/S), relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In one study, Quercus robur L. (fruit cups) extract was used as a natural dye, and Salix alba L. wood extract was used as a bio-mordant for dyeing wool and pashmina fabrics. It is reported that the extracted dye displayed a diversity of color tones when used in combination with natural mordants using various mordanting techniques (Geelani et al 2015 ). In another study, Kavak et al ( 2010 ) used onion peel ( Allium cepa ) as a natural dye, willow ( Salix alba ) extract as a bio-mordant, and AAUS (Artifical Animal Urine System) together to dye wool, cotton, feathered-leather fibers, and wood materials.…”
Section: Mordant Agentsmentioning
confidence: 99%
“…In one study, Quercus robur L. (fruit cups) extract was used as a natural dye, and Salix alba L. wood extract was used as a bio-mordant for dyeing wool and pashmina fabrics. It is reported that the extracted dye displayed a diversity of color tones when used in combination with natural mordants using various mordanting techniques (Geelani et al 2015 ). In another study, Kavak et al ( 2010 ) used onion peel ( Allium cepa ) as a natural dye, willow ( Salix alba ) extract as a bio-mordant, and AAUS (Artifical Animal Urine System) together to dye wool, cotton, feathered-leather fibers, and wood materials.…”
Section: Mordant Agentsmentioning
confidence: 99%
“…Apparently, the protein nature of wool fibers has better affinity to T. australis and P. murcianum dyes than the cellulosic linen fibers, even when the dyes are carried in ethanol. This is not surprising since it is known that fibers of animal origin such as wool have greater affinity for natural dyes than cellulosic fibers, which often require treatments with more than one mordant to improve the color fastness (Geelani et al, 2013;Prabhu and Bhute, 2012). The exact chemical structure of the fungal dyes used in this work is still on research.…”
Section: A Color Version Of This Figure Is Available Onlinementioning
confidence: 99%
“…They may cause carcinogenic, toxic, and allergic effects, especially on humans. Therefore, natural dyes and pigments can be considered as very important alternatives to synthetic dyes (2)(3)(4). In addition, there is a growing interest in recent years for the use of natural dyes by researchers due to their biodegradable, nonallergenic, non-toxic, and environmentally friendly properties (5,6).…”
Section: Introductionmentioning
confidence: 99%